A plastic crystal phosphate coated spinel lithium manganate composite material, a preparation method and application thereof

CN122992008APending Publication Date: 2026-10-27VKAN CERTIFICATION & TESTING +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511003924.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

该复合正极材料具有较高的结构稳定性,能够减少电极/电解液界面副反应,提高电极/电解液界面稳定性;不过,该专利通过两步法进行掺杂与包覆,掺杂过程主要通过固相反应进行,不利于均匀掺杂而影响效果

Benefits of technology

[0031]本发明通过在尖晶石锰酸锂基体材料表面包塑晶磷酸盐材料,能显著提升材料表面的电子迁移和离子扩散,从而提升其电化学反应速率,实现优异快充性能。此外,塑晶磷酸盐具有优异的化学和电化学稳定性,可以抑制电解液的侵蚀等副反应的发生。同时,在塑晶包覆过程中,在尖晶石锰酸锂的亚表层会形成杂原子掺杂的尖晶石锰酸锂,进而提高尖晶石锰酸锂的结构稳定性,改性后得到的复合材料具备优异的倍率性能和循环性能,且兼具安全性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992008A_ABST
    Figure CN122992008A_ABST
Patent Text Reader

Abstract

The application discloses a plastic crystal phosphate coated spinel lithium manganate composite material, characterized in that the material comprises a base material and a coating layer coated on the surface of the base material; the base material is spinel lithium manganate; and the coating layer is plastic crystal phosphate, and the general formula of the plastic crystal phosphate is Li y M x PO4, wherein the M element comprises at least one of Mg, Al, Zn, Ca, Sr, Se, Mo and W. The application further discloses a preparation method and application of the plastic crystal phosphate coated spinel lithium manganate composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrode materials technology, and more specifically, to a plastic crystalline phosphate-coated spinel lithium manganese oxide composite material, its preparation method, and its application. Background Technology

[0002] Driven by both policy and market forces, my country's new energy vehicle (NEV) market continued its explosive growth in 2024, with production and sales reaching 12.888 million and 12.866 million units respectively, representing year-on-year increases of 34.4% and 35.5%. NEV sales accounted for 40.9% of total new vehicle sales. As the "heart" of NEVs, the production, sales, and installation volume of power batteries also experienced explosive growth, driven by the NEV market. Notably, lithium iron phosphate (LFP) batteries, one of the two main types of power batteries, saw significantly higher production, sales, installation volume, and growth rates than ternary lithium batteries. Furthermore, my country's NEV market is currently dominated by A-class vehicles, with plug-in hybrid and range-extended electric vehicles developing rapidly. Therefore, low-cost, high-safety power batteries have become the mainstream development strategy. Especially given the fluctuating price of battery-grade lithium carbonate, the future will still be dominated by low-cost, high-safety power batteries, and the price and thermal stability of cathode materials will largely determine the cost and safety of power batteries.

[0003] Currently, spinel LiMn2O4 is the lowest-priced, cobalt-free, low-cost cathode material for power batteries. However, in practical applications, it faces problems such as poor cycle stability and insufficient rate performance, severely restricting its widespread use in the power battery field. Nevertheless, spinel LiMn2O4 possesses advantages such as low price, high thermal stability, and environmental friendliness, which highly align with the current development direction of power battery cathode materials. Therefore, developing high-rate, long-cycle spinel LiMn2O4 cathode materials can effectively overcome the "range anxiety" and "cost pressure" of new energy vehicles.

[0004] However, spinel LiMn2O4 has Mn content. 3+ The inherent Jahn-Teller effect and spontaneous disproportionation reaction cause severe irreversible structural distortion and manganese dissolution during lithium-ion insertion / extraction, ultimately leading to continuous voltage and capacity decay during cycling, severely restricting its widespread use in power batteries. Therefore, the biggest challenge is to mitigate the Jahn-Teller effect and spontaneous disproportionation reaction in spinel LiMn2O4 to improve its structural and interfacial stability, thereby enhancing voltage and capacity retention during cycling. Currently, the main approaches to addressing the Jahn-Teller effect and spontaneous disproportionation reaction in spinel LiMn2O4 are elemental doping and surface coating to improve its overall electrochemical performance.

[0005] The purpose of element doping is to modify materials. Commonly used doping elements include Mg, Al, and Zn. For lithium manganese oxide materials, element doping can effectively suppress Jahn-Teller distortion while maintaining the spinel structure, thereby improving its structural stability during cycling. Admittedly, element doping can improve the structural stability of spinel LiMn2O4 to a certain extent, but it cannot suppress side reactions at the electrode / electrolyte interface, and therefore cannot effectively alleviate the problem of manganese dissolution. For example, Chinese patent CN1455466A discloses a method for preparing structurally stable spinel lithium manganese oxide for lithium-ion batteries. The method involves uniformly mixing electrolytic manganese dioxide (10-20 μm particle size), lithium carbonate (5-10 μm particle size), and cobalt oxide (5-10 μm particle size), followed by multi-component doping and high-temperature solid-state sintering. The mass percentages are: 70-72% electrolytic manganese dioxide (MnO2) with a content greater than 92%, 15-17% lithium carbonate (Li2CO3) with a content greater than 99.9%, 10-20% cobalt oxide (CoO) with a content greater than 70%, and 1-3% multi-component dopant composed of nickel (Ni), chromium (Cr), iron (Fe), manganese (Mg), selenium (Si), and fluorine (F). This method can only achieve doping modification of the spinel lithium manganese oxide cathode material; it cannot achieve cathode material coating during the doping process, which is detrimental to improving the stability of the electrode / electrolyte interface.

[0006] Surface coating is a widely commercially used interface modification measure that can effectively alleviate side reactions at the electrode / electrolyte interface. Commonly used coating layers include oxides, fluorides, and phosphates. However, coating modification has the following drawbacks: (1) Due to the different radii of curvature of heterogeneous coating sources, heterogeneous coating is prone to forming island-like coating layers, which cannot provide full-area protection for the electrode material; (2) Coating modification can only alleviate side reactions at the electrode / electrolyte interface and cannot suppress Jahn-Teller distortion, so it cannot improve structural stability. For example, Chinese patent CN119340359A discloses a manganese-based cathode material coated with a solid electrolyte. Its preparation method includes the following steps: S1, mixing a spherical spinel lithium manganese oxide precursor with a graphene solution and reacting it under microwave assistance at 100-150°C to obtain carbon-coated spinel lithium manganese oxide; S2, adding soluble lithium source I, titanium source, aluminum source, and phosphorus source to a mixture containing citric acid, ethylene glycol, and water to obtain a mixed solution, adding the carbon-coated spinel lithium manganese oxide to the mixed solution, and reacting under heating conditions to form a gel mixture; S3, aging and drying the gel mixture, followed by calcination to obtain the manganese-based cathode material coated with a solid electrolyte. This method can only achieve coating modification of the spinel lithium manganese oxide cathode material and cannot achieve subsurface doping during the coating process, which is detrimental to improving the structural stability of the spinel lithium manganese oxide.

[0007] Therefore, a single modification measure cannot simultaneously improve the structural and interfacial stability of spinel LiMn2O4. Thus, developing efficient synergistic modification measures is crucial for mitigating the capacity decay and voltage drop of spinel LiMn2O4. Existing technologies also report on the preparation of cathode materials from spinel LiMn2O4 through elemental doping and surface coating. For example, Chinese patent CN119725436A discloses a composite cathode material and its application. The composite cathode material includes a core and an outer layer coating the core. The core includes yttrium-doped cathode material, and the outer layer includes phosphate. In the core, the doping amount of yttrium is 0.01–3 wt%; the coating amount in the outer layer accounts for 0.01–5 wt% of the composite cathode material. This composite cathode material exhibits high structural stability, reduces side reactions at the electrode / electrolyte interface, and improves the stability of the electrode / electrolyte interface. However, this patent uses a two-step doping and coating method, with the doping process mainly occurring through solid-phase reactions, which is not conducive to uniform doping and affects the overall performance. Summary of the Invention

[0008] In view of the above-mentioned technical problems existing in the prior art, the present invention provides a plastic crystal phosphate coated spinel lithium manganese oxide composite material, which has excellent rate performance and cycle performance.

[0009] To achieve the above objectives, the present invention adopts the following technical solution.

[0010] A crystalline phosphate-coated spinel lithium manganese oxide composite material, characterized in that it comprises a matrix material and a coating layer covering the surface of the matrix material; the matrix material is lithium spinel manganese oxide; the coating layer is a crystalline phosphate, the general formula of which is Li. y M x PO4, wherein the element M includes at least one of Mg, Al, Zn, Ca, Sr, Se, Mo and W.

[0011] This invention significantly enhances the electron migration and ion diffusion rates of a spinel lithium manganese oxide matrix by coating it with a plastic phosphate material, thereby increasing ionic and electronic conductivity and ultimately improving electrochemical reaction rates for superior fast-charging performance. Furthermore, the plastic phosphate exhibits excellent chemical and electrochemical stability, suppressing side reactions such as electrolyte erosion. Simultaneously, during the plastic phosphate coating process, heteroatom-doped spinel manganese oxide forms in the subsurface layer of the spinel manganese oxide, further improving its structural stability. The resulting composite material possesses excellent rate performance and cycle life. Moreover, the plastic phosphate exhibits long-range order but highly short-range disorder, which is beneficial for uniform coating on the surface of the spinel manganese oxide matrix.

[0012] Preferably, the general formula of the plastic crystal phosphate is Li y M x In PO4, 0 <x<3,0<y<3,0<x+y<3。

[0013] Preferably, the molar ratio of the matrix material to the crystalline phosphate is 1:0.1 to 1:0.005. Specifically, the coating layer thickness is 10 to 1000 nm, and can be 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, 1000 nm, etc. A crystalline phosphate coating layer of a certain thickness can significantly improve the electronic and ionic conductivity and stability of the cathode material surface, thereby improving the rate performance and cycle life of the battery.

[0014] This invention provides a method for preparing the aforementioned crystalline phosphate-coated spinel lithium manganese oxide composite material, the method comprising the following steps:

[0015] S1. Weigh the lithium source and manganese source according to the stoichiometric ratio, add them to water and mix evenly to obtain a mixed slurry; after spray drying the mixed slurry, pre-sinter it in an oxygen atmosphere by first heating it to 500℃, and then heating it to 800~1000℃ for secondary sintering to obtain spinel lithium manganese oxide matrix material.

[0016] S2, according to the general formula of plastic crystal phosphate Li y M x PO4, weigh out lithium source, M element source and phosphorus source, then mix with the matrix material obtained in step S1, ball mill and dry; place in an inert atmosphere, first heat to 500℃ for pre-sintering, then heat to 800~1000℃ for sintering, to obtain plastic crystal phosphate coated spinel lithium manganese oxide composite material.

[0017] In some embodiments, in step S1, the lithium source, manganese source, and water are mixed evenly in a ball mill to obtain a mixed slurry. The lithium source, manganese source, and water can be mixed in any solid-liquid ratio to achieve the purpose of this invention; of course, the lithium source and manganese source can also achieve the purpose of this invention by dry ball milling without adding water.

[0018] In some embodiments, in step S1, the inlet air temperature of the spray dryer is 100-300°C, the outlet air temperature is 60-160°C, the nozzle diameter is 0.3-3.0 mm, the air source is compressed air, which is preheated to 70-280°C before entering the spray gun, and the spray feed flow rate is 400-7000 mL / h.

[0019] In some embodiments, in step S1, the temperature is first raised to 500°C for pre-sintering for 3-5 hours in an oxygen atmosphere, and then raised to 800-1000°C for secondary sintering for 5-8 hours to obtain spinel lithium manganese oxide matrix material.

[0020] In some embodiments, in step S1, the lithium source is at least one selected from lithium carbonate, lithium hydroxide, lithium bicarbonate, lithium dihydrogen phosphate, lithium pyrophosphate, lithium dihydrogen pyrophosphate, lithium acetate, and lithium citrate.

[0021] In some embodiments, the manganese source is at least one of manganese oxide, manganese hydroxide, manganese chloride, manganese sulfate, manganese carbonate, and manganese sulfide.

[0022] In some embodiments, the phosphorus source is at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and phosphoric acid.

[0023] In some embodiments, the source of element M is an inorganic salt containing element M, such as aluminum, which can be at least one of aluminum chloride, aluminum sulfate, aluminum nitrate, sodium aluminate, aluminum phosphate, aluminum dihydrogen phosphate, and basic aluminum carbonate.

[0024] In some embodiments, in step S2, the temperature is first raised to 500°C for pre-sintering for 2-5 hours, and then raised to 800-1000°C for sintering for 5-8 hours to obtain a plastic crystalline phosphate-coated spinel lithium manganese oxide composite material.

[0025] In some embodiments, in step S2, the inert atmosphere is one of nitrogen, argon, or helium.

[0026] In some embodiments, in step S2, the ball milling rate is 300-900 r / min and the ball milling time is 0.5-5 h.

[0027] The present invention also provides a positive electrode comprising the aforementioned crystalline phosphate-coated spinel lithium manganese oxide composite material.

[0028] The present invention also provides an electrochemical energy storage device, which includes the aforementioned positive electrode.

[0029] Specifically, the electrochemical energy conversion device includes lithium-ion batteries, lithium-ion capacitors, etc.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] This invention significantly enhances electron migration and ion diffusion on the surface of a spinel lithium manganese oxide matrix by coating it with a plastic crystalline phosphate material, thereby increasing the electrochemical reaction rate and achieving excellent fast-charging performance. Furthermore, the plastic crystalline phosphate exhibits excellent chemical and electrochemical stability, suppressing side reactions such as electrolyte erosion. Simultaneously, during the plastic coating process, heteroatom-doped spinel manganese oxide is formed in the subsurface layer of the spinel manganese oxide, further improving its structural stability. The resulting composite material possesses excellent rate performance and cycle performance, while also ensuring safety.

[0032] The spinel lithium manganese oxide composite material coated with plasticized phosphate according to the present invention exhibits excellent rate performance and cycle stability when applied in electrochemical energy conversion devices. Furthermore, the preparation method of the present invention is simple, employing an in-situ reaction route, which facilitates uniform distribution of the plasticized phosphate coating layer, possesses high versatility, is suitable for industrial applications, and helps to expand the large-scale application of spinel lithium manganese oxide cathode materials. Attached Figure Description

[0033] Figure 1 The first charge-discharge specific capacity curves of the comparative sample and the blank sample in Example 1 are shown.

[0034] Figure 2 The curves showing the change in discharge specific capacity of the comparative sample and blank sample in Example 2 as the number of cycles increases under a voltage of 3.2–4.3V and a current density of 2C.

[0035] Figure 3 This is an electron microscope image of the crystalline phosphate-coated spinel lithium manganese oxide composite material of Example 3.

[0036] Figure 4 The X-ray diffraction results are for the plastic crystal phosphate coating layer in Example 3.

[0037] Figure 5 The elemental distribution diagram of the subsurface layer of the spinel lithium manganese oxide composite material coated with plastic crystal phosphate. Detailed Implementation

[0038] Numerous specific details are set forth in the following description to provide a full understanding of the invention. However, the invention can be practiced in many other ways different from those described herein, and similar modifications can be made by those skilled in the art without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0040] The testing method for the cathode material of this invention is as follows:

[0041] Electrochemical performance testing primarily used coin cells as the test substrate. The working electrode in the coin cell was composed of an active material (spinel LiMn2O4 cathode material prepared in the examples), conductive carbon (Ketjen Black), and polyvinylidene fluoride (PVDF) binder in a mass ratio of 70%:20%:10%. The electrode preparation process was as follows: After uniformly mixing the active material and conductive carbon, the mixture was added to a solution of N-methylpyrrolidone (1-Methyl-2-Pyrrolidone, NMP) containing PVDF, and the mixture was prepared into a uniform viscous consistency. The viscous slurry was then uniformly coated onto aluminum foil, and the coated aluminum foil was dried in a vacuum drying oven at 120°C for 12 hours. The dried electrode sheets were cut into 14mm diameter pieces using a cutting machine. These electrode sheets were then assembled with 16mm diameter lithium sheets in an inert atmosphere (high-purity argon, 99.999%) glove box to form a CR2016 coin cell. The charge-discharge curves and rate performance curves of the battery were obtained using a Blue Electric testing system.

[0042] Example 1

[0043] A method for preparing a crystalline phosphate-coated spinel lithium manganese oxide composite material includes the following steps:

[0044] S1. 77.58g of lithium carbonate and 229.9g of manganese carbonate were added to 3L of deionized water and stirred in a ball mill at 600rpm for 4 hours to obtain a slurry. The slurry was then pumped to a spray dryer with a nozzle diameter of 2mm. Compressed air was preheated at 100℃, the feed rate was 2500mL / h, the inlet air temperature was 150℃, and the outlet air temperature was 150℃ to obtain dried particles. The particles were then sintered in an oxygen atmosphere at a rate of 8℃ / min to 500℃ for 5 hours, and then sintered again at a rate of 5℃ / min to 900℃ for 5 hours to obtain a spinel lithium manganese oxide matrix material, which served as the blank sample for this embodiment.

[0045] S2. Mix 180g of spinel lithium manganese oxide matrix material, 0.554g of lithium carbonate, 0.885g of aluminum sulfate, and 1.15g of ammonium dihydrogen phosphate material. The theoretical molar ratio of the plastic crystal coating layer to the spinel lithium manganese oxide matrix material is 0.01:1. The mixture is ball-milled at 600 rpm for 1 hour, then dried in a vacuum drying oven at 80°C for 5 hours. Next, it is sintered in a nitrogen atmosphere at a rate of 5°C / min to 500°C for 2 hours, followed by a second sintering at 5°C / min to 900°C for 5 hours to obtain plastic crystal phosphate (Li...). 1.5 Al 0.5 A spinel lithium manganese oxide composite material coated with PO4 was used as a comparative sample in this embodiment.

[0046] After testing, such as Figure 1 As shown, the blank sample obtained in this embodiment has initial charge-discharge specific capacities of 144.8 mAh / g and 110.2 mAh / g at a voltage of 3.2–4.3 V and a current density of 0.1 C, respectively, corresponding to an initial coulombic efficiency of 76%. The comparative sample obtained in this embodiment has initial charge-discharge specific capacities of 127.5 mAh / g and 117.3 mAh / g at a voltage of 3.2–4.3 V and a current density of 0.1 C, respectively, corresponding to an initial coulombic efficiency of 92%.

[0047] Example 2

[0048] A method for preparing a crystalline phosphate-coated spinel lithium manganese oxide composite material includes the following steps:

[0049] S1. 77.58g of lithium carbonate and 229.9g of manganese carbonate were added to 3L of deionized water and stirred in a ball mill at 600rpm for 4 hours to obtain a slurry. The slurry was then pumped to a spray dryer with a nozzle diameter of 2mm. Compressed air was preheated at 100℃, the feed rate was 2500mL / h, the inlet air temperature was 150℃, and the outlet air temperature was 150℃ to obtain dried particles. The particles were then sintered in an oxygen atmosphere at a rate of 5℃ / min to 500℃ for 5 hours, and then sintered again at a rate of 5℃ / min to 1000℃ for 5 hours to obtain a spinel lithium manganese oxide matrix material, which served as the blank sample for this embodiment.

[0050] S2. Mix 180g of spinel lithium manganese oxide matrix material, 0.554g of lithium carbonate, 0.885g of aluminum sulfate, and 1.15g of ammonium dihydrogen phosphate material. The theoretical molar ratio of the plastic crystal coating layer to spinel lithium manganese oxide is 0.01:1. Ball mill the mixture at 600 rpm for 1 hour, then dry it in a vacuum drying oven at 80°C for 5 hours. Next, sinter it in a nitrogen atmosphere at a rate of 5°C / min to 500°C for 2 hours, and then sinter it again at a rate of 5°C / min to 1000°C for 5 hours to obtain plastic crystal phosphate (Li...). 1.5 Al 0.5 A spinel lithium manganese oxide composite material coated with PO4 was used as a comparative sample in this embodiment.

[0051] After testing, such as Figure 2 As shown, the composite material obtained in this embodiment was cycled 153 times at a voltage of 3.2 to 4.3V and a current density of 2C. The cycle retention rate of the comparison sample was 96.1%, which was significantly higher than the 43.5% of the blank sample.

[0052] Example 3

[0053] A method for preparing a crystalline phosphate-coated spinel lithium manganese oxide composite material includes the following steps:

[0054] S1. 77.58g of lithium carbonate and 229.9g of manganese carbonate were added to 3L of deionized water and stirred in a ball mill at 600rpm for 4 hours to obtain a slurry. The slurry was then pumped to a spray dryer with a nozzle diameter of 2mm. Compressed air was preheated at 100℃, the feed rate was 2500mL / h, the inlet air temperature was 150℃, and the outlet air temperature was 150℃ to obtain dried particles. The particles were then sintered in an oxygen atmosphere at a rate of 5℃ / min to 500℃ for 5 hours, and then sintered again at a rate of 5℃ / min to 1000℃ for 5 hours to obtain a spinel lithium manganese oxide matrix material.

[0055] S2. Mix 180g of spinel lithium manganese oxide matrix material, 1.08g of lithium carbonate, 0.042g of aluminum sulfate, and 1.15g of ammonium dihydrogen phosphate material. The theoretical molar ratio of the plastic crystal coating layer to spinel lithium manganese oxide is 0.01:1. Ball mill at 900 rpm for 1 hour, then dry in a vacuum drying oven at 80°C for 5 hours. Next, sinter in a nitrogen atmosphere at 500°C for 3 hours, then sinter again at 1000°C for 6 hours, yielding plastic crystal phosphate (Li...). 2.925 A 0.025 PO4) coated spinel lithium manganese oxide composite material.

[0056] Plasticized phosphate-coated spinel lithium manganese oxide composite materials, such as Figure 3 As shown in the figure, the left side of the figure shows the coating layer and the subsurface layer of spinel lithium manganese oxide, where the coating layer is about 10 nm thick.

[0057] Depend on Figure 4 It can be seen that the prepared Li 2.925 Al 0.025 The high matching degree of X-ray diffraction peaks between PO4 and plastic phosphate (PDF card: 01-084-0197) indicates that the phosphate obtained by this method is plastic phosphate.

[0058] Depend on Figure 5 It is evident that aluminum doping was achieved in the subsurface layer of the spinel lithium manganese oxide composite material.

[0059] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0060] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A crystalline phosphate-coated spinel lithium manganese oxide composite material, characterized in that, It includes a matrix material and a coating layer covering the surface of the matrix material; the matrix material is spinel lithium manganese oxide; the coating layer is a plastic crystalline phosphate, the general formula of which is Li. y M x PO4, wherein the element M includes at least one of Mg, Al, Zn, Ca, Sr, Se, Mo and W; the molar ratio of the matrix material to the plastic crystal phosphate is 1:0.1 to 1:0.

005.

2. The crystalline phosphate-coated spinel lithium manganese oxide composite material according to claim 1, characterized in that, The general formula of the plastic phosphate is Li. y M x In PO4, 0 <x<3,0<y<3,0<x+y<3。 3. The method for preparing the plastic crystalline phosphate-coated spinel lithium manganese oxide composite material according to claim 1 or 2, characterized in that, Includes the following steps: S1. Weigh the lithium source and manganese source according to the stoichiometric ratio, add them to water and mix evenly to obtain a mixed slurry; after spray drying the mixed slurry, pre-sinter it in an oxygen atmosphere by first heating it to 500℃, and then heating it to 800~1000℃ for secondary sintering to obtain spinel lithium manganese oxide matrix material. S2, according to the general formula of plastic crystal phosphate Li y M x PO4, weigh out lithium source, M element source and phosphorus source, then mix with the matrix material obtained in step S1, ball mill and dry; place in an inert atmosphere, first heat to 500℃ for pre-sintering, then heat to 800~1000℃ for sintering, to obtain plastic crystal phosphate coated spinel lithium manganese oxide composite material.

4. The preparation method of the plastic crystalline phosphate-coated spinel lithium manganese oxide composite material according to claim 3, characterized in that, In step S1, the lithium source, manganese source and water are mixed evenly in a ball mill to obtain a mixed slurry; the inlet air temperature of the spray dryer is 100-300℃ and the outlet air temperature is 60-160℃; the nozzle diameter is 0.3-3.0mm, the air source is compressed air, which is preheated to 70-280℃ before entering the spray gun; the spray feed flow rate is 400-7000mL / h.

5. The preparation method of the plastic crystal phosphate-coated spinel lithium manganese oxide composite material according to claim 4, characterized in that, In step S1, in an oxygen atmosphere, the temperature is first raised to 500°C for pre-sintering for 3-5 hours, and then raised to 800-1000°C for secondary sintering for 5-8 hours to obtain spinel lithium manganese oxide matrix material.

6. The method for preparing the plastic crystalline phosphate-coated spinel lithium manganese oxide composite material according to claim 5, characterized in that, The lithium source is at least one of lithium carbonate, lithium hydroxide, lithium bicarbonate, lithium dihydrogen phosphate, lithium pyrophosphate, lithium dihydrogen pyrophosphate, lithium acetate, and lithium citrate; the manganese source is at least one of manganese oxide, manganese hydroxide, manganese chloride, manganese sulfate, manganese carbonate, and manganese sulfide; the phosphorus source is at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and phosphoric acid; and the M element source is an inorganic salt containing the M element.

7. The method for preparing the plasticized phosphate-coated spinel lithium manganese oxide composite material according to claim 6, characterized in that, In step S2, the temperature is first raised to 500℃ for pre-sintering for 2-5 hours, and then raised to 800-1000℃ for sintering for 5-8 hours to obtain a plastic crystalline phosphate-coated spinel lithium manganese oxide composite material; the inert atmosphere is one of nitrogen atmosphere, argon atmosphere, and helium atmosphere.

8. The method for preparing the plastic crystalline phosphate-coated spinel lithium manganese oxide composite material according to claim 7, characterized in that, In step S2, the ball milling rate is 300-900 r / min and the ball milling time is 0.5-5 h.

9. A positive electrode, characterized in that, The composite material includes the plastic crystal phosphate coated spinel lithium manganese oxide as described in claim 1 or 2.

10. An electrochemical energy storage device, characterized in that, Includes the positive electrode as described in claim 9.

Citation Information

Patent Citations

  • Manganese-based positive electrode material coated with solid electrolyte as well as preparation method and application of manganese-based positive electrode material

    CN119340359A

  • Composite positive electrode material and application thereof

    CN119725436A

  • Spinel lithium manganate with stable structure for lithium ion cell and manufacturing method thereof

    CN1455466A